(untitled) (Global Journal of Science Frontier Research, 2013)
The present study was carried out to develop ice cream using frozen Kinnow peel; both unblanched and blanched, at the levels of 1, 3 and 5%, each. The ice cream samples were analyzed for sensory and chemical parameters. The addition of Kinnow peel improved the appearance, flavour and overall acceptability of the ice cream samples. The total solids (TS), ascorbic acid and flavonoids (naringin) content of the ice cream samples were found to increase with increased level of addition of peel. Based on sensory evaluation, the best levels of frozen Kinnow peel in ice cream were: unblanched-3% and blanched-5%. When compared, ice cream with 3% unblanched-frozen kinnow peel was found to be the best.